ANALISIS KESULITAN PESERTA DIDIK DALAM PENYELESAIAN SOAL HOTS TENTANG DINAMIKA ROTASI PADA KELAS XI - Rizki Amalia; Stepanus Sahala Sitompul; M. Musa Syarif H. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research aims to reveal the profile, the percentage and to find out the causes of students’ difficulties in solving about rotational dynamics and statistic equilibrium. This Research conducted at MAN 2 Pontianak which subjects are 5 out of 20 students who were given the test. Data collected by giving the HOTS essay questions and interviews. The analysis data technic was Miles and Huberman. The results show that students' difficulties are divided into 5 according to the Heller problem solving stages. (1) The difficulty of visualizing the problems by students was 63.75%. Because they do not know how to draw a sketch on each question. (2) The difficulty of physics description by students was 21.25 %. Because they do not understand the problems given to the questions. (3) The difficulty of making the plan solution was 58,75%. Because they do not understand the concepts used in the questions. (4) The difficulty of executing the plan was 71,25%. Because they do not know the concepts used in the questions and do not understand the arithmetic operations. (5) The difficulty of checking and evaluating was 78,75%. Because they are not careful in checking the answers and being hurry to finish the questionsKeywords: Analysis Difficulty, Problem Solving HOTS, Rotational Dynamics and Statistic Equilibrium